Benefits Of Multicultural Society From Various Fields - Hayati, Eza Qurnia; Suradi, A.; Bahrun, Khairul; Pratama, M. Arifky (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study discusses the significant advantages of a multicultural society through an analysis of relevant literature. Cultural diversity in a multicultural society not only enriches individual experiences but also enhances understanding of various values. Intercultural interaction creates cultural enrichment that broadens horizons and communication skills, allowing individuals to better adapt to diverse environments. Multicultural societies also serve as drivers of creativity and innovation, where cross-cultural collaboration generates new ideas and creative solutions to existing challenges. In addition, cultural diversity contributes to economic growth through trade, investment, and tourism, which supports the prosperity of society. Mutual learning in a multicultural context enhances empathy, tolerance, and critical thinking skills, which are important in an increasingly complex world. Living in a multicultural society also strengthens tolerance and global awareness, supporting universal values ??such as unity and justice. This study uses a qualitative literature review method, with sources from credible secondary literature. It is hoped that this study will provide in-depth insights into the advantages of a multicultural society and become a basis for further research Keberagaman budaya, inovasi dan sosial, pertumbuhan Ekonomi, Masyarakat Multikultural